2022
DOI: 10.1111/brv.12885
|View full text |Cite
|
Sign up to set email alerts
|

Avian adjustments to cold and non‐shivering thermogenesis: whats, wheres and hows

Abstract: Avian cold adaptation is hallmarked by innovative strategies of both heat conservation and thermogenesis. While minimizing heat loss can reduce the thermogenic demands of body temperature maintenance, it cannot eliminate the requirement for thermogenesis. Shivering and non-shivering thermogenesis (NST) are the two synergistic mechanisms contributing to endothermy. Birds are of particular interest in studies of NST as they lack brown adipose tissue (BAT), the major organ of NST in mammals. Critical analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 320 publications
0
7
0
Order By: Relevance
“…On the other hand, Swanson et al (2023) carried out a literature review investigating flexibility in BMR, M sum and metabolic expansibility, and found that, in fact, for none of the six species for which data were available, higher levels of flexibility in M sum or metabolic expansibility did not typically result in increased maintenance costs (i.e., BMR). This suggests that non‐shivering thermogenesis mechanisms may also contribute significantly to thermoregulation in birds (Pani & Bal, 2022). Indeed, multiple adaptations at the cellular and biochemical level have been shown to affect an organism's thermogenic capacity when exposed to changing temperatures (Milbergue et al, 2018; Swanson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Swanson et al (2023) carried out a literature review investigating flexibility in BMR, M sum and metabolic expansibility, and found that, in fact, for none of the six species for which data were available, higher levels of flexibility in M sum or metabolic expansibility did not typically result in increased maintenance costs (i.e., BMR). This suggests that non‐shivering thermogenesis mechanisms may also contribute significantly to thermoregulation in birds (Pani & Bal, 2022). Indeed, multiple adaptations at the cellular and biochemical level have been shown to affect an organism's thermogenic capacity when exposed to changing temperatures (Milbergue et al, 2018; Swanson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Egg formation in birds requires a high basal metabolism (around 37-55% of the total energy budget for small passerines) and a sufficient supply of macro-and micro-nutrients (Reynolds and Perrins 2010). Hence, females may need to trade off the energy expenditure between egg-laying and thermoregulation in the early breeding season (Dhondt and Eycherman 1979, Yom-Tov and Wright 1993, Meijer et al 1999, or possibly decrease energy expenditure through night hypothermia as in other passerine species (Cooper and Gessaman 2005, Ruf and Geiser 2015, Pani and Bal 2022. Furthermore, the drongos our study population overwinter in the tropics and typically experience warm temperatures year-round.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study was to determine whether the skeletal muscles of Brandt's voles produce heat at low temperature and whether they can compensate for thermogenesis when BAT function is minimized. The reason why we chose to remove iBAT instead of UCP1 −/− is that conditional ablation of iBAT is superior to using an UCP1 −/− model, which was discovered to be highly heterogeneous in cold sensitivity for mice with different genetic backgrounds [30]. In addition, since Brandt's voles do not have a mature UCP1 −/− model, we removed the interscapular BAT by surgery to minimize the BAT function.…”
Section: Discussionmentioning
confidence: 99%
“…When BAT function is acutely minimized, skeletal muscle becomes the major site of NST during cold acclimation, and muscle thermogenesis depends on SER Ca 2+ handling and mitochondrial remodeling. The muscle NST as a thermogenic mechanism must have been wired into the vertebrate body quite early in the evolution and might play even greater roles in birds (where BAT is absent) and larger mammals (where BAT becomes a minor component in adulthood) [30]. At the early stage of evolution, birds lost the UCP1 gene from their genomes, and completely lacked the BAT-like structure [31][32][33].…”
Section: Discussionmentioning
confidence: 99%